Practicing Level and Determinants of Safe Cord Care and Skin-To-Skin Contact Among Post-partum Women in Public Hospitals of Eastern Ethiopia - Eyeberu, Addis; Getachew, Tamirat; Debella, Adera; Birhanu, Abdi; Alemu, Addisu; Dessie, Yadeta (Frontiers in Pediatrics, 2022)
Background Even though practicing levels of safe cord care and skin-to-skin contact among post-partum women are critical to reducing neonatal deaths, limited data revealed the low practice. Thus, the purpose of this study was to determine the level of practice and determinants of safe cord care and skin-to-skin contact among post-partum women in public hospitals of Eastern Ethiopia. Methods A facility-based cross-sectional study was conducted at the public hospitals of Harari reginal state, eastern Ethiopia. A random sample of 820 post-partum women was included in the study. A pre-tested and structured questionnaire was used to collect data through a face-to-face interview. STATA version 14 was used for data analysis. Bivariable and multivariable logistic regression analyses were employed to determine the association between independent and outcome variables. Results The practicing level of safe cord care was 71.7% (95% Confidence Interval (CI): 64.5, 81.7). While the practicing level of Skin-To-Skin contact was 53.2% (95% CI: 43.6, 58.8). Being in age of 20–29 [adjusted odds ratio (AOR) = 2.93, 95% CI: 1.24, 6.96], attending tertiary education [AOR = 1.83, 95% CI (1.08, 3.13)], and having good knowledge about safe cord care [AOR = 11.3, 95% CI: (7.49, 17.18)] were determinants of safe cord care practice. While mothers aged 20–29, 30–39, and above 40 [(AOR = 11.17, 95% CI: 4.71, 26.5; AOR = 4.1, 95% CI: 1.77, 9.55, and AOR = 14.3, 95% CI: 7.2, 28.6), respectively], Being married [AOR = 3.70, 95% CI (1.58, 8.70)], being a merchant and self-employed ([AOR = 0.55, 95% CI: 0.34,0.87] and [AOR = 0.49, 95% CI: 0.27, 0.86], respectively), having good knowledge about SSC [AOR = 2.11, 95% CI: (1.53, 2.92)], giving birth at gestational age of 37–42 weeks [AOR = 1.82, 95% CI (1.31, 2.5)], and multigravidity (AOR = 2.83, 95% CI (1.90,4.21) were significantly associated with skin to skin contact. Conclusions The practicing level of safe cord care and skin-to-skin contact was high. In this study, the age of mothers, educational status, and knowledge of post-partum women on safe cord care were determinants of a safe cord care practice. While the age of mothers, marital status, occupational status, knowledge of mother, and gestational age at birth were significantly associated with skin-to-skin contact practice. Safe cord care should be strengthened and intensified to reduce neonatal mortality due to avoidable umbilical cord infections. Furthermore, skin-to-skin contact practice should be strengthened to enhance the survival of at-risk neonates.